2017
DOI: 10.1016/j.immuni.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Macrophages Are Locally Programmed for Silent Clearance of Apoptotic Cells

Abstract: SUMMARY Although apoptotic cells (ACs) contain nucleic acids that can be recognized by Toll-like receptors (TLRs), engulfment of ACs does not initiate inflammation in healthy organisms. Here we identified macrophage populations that continually engulf ACs in distinct tissues and found that these macrophages shared characteristics compatible with immunologically silent clearance of ACs, including high expression of AC recognition receptors, low expression of TLR9, and reduced TLR responsiveness to nucleic acids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(195 citation statements)
references
References 72 publications
8
186
0
1
Order By: Relevance
“…Macs likely undergo sequential functional switches in response to pathogen exposure, and signals from other immune and tissue resident stromal cells, which are essential for coordinated responses, removal of nonself/altered‐self, adaptive immunity and tissue repair . In steady state, tissue resident Macs seem to be programmed for uptake of dying cells by phagocytosis and elimination through lymphatics in a process called efferocytosis . Efferocytosis is thought to be a critical process in which regulatory interactions between target and effector cells determine its outcome .…”
Section: Mac Functions In Inflammation Resolution and Osteoimmunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Macs likely undergo sequential functional switches in response to pathogen exposure, and signals from other immune and tissue resident stromal cells, which are essential for coordinated responses, removal of nonself/altered‐self, adaptive immunity and tissue repair . In steady state, tissue resident Macs seem to be programmed for uptake of dying cells by phagocytosis and elimination through lymphatics in a process called efferocytosis . Efferocytosis is thought to be a critical process in which regulatory interactions between target and effector cells determine its outcome .…”
Section: Mac Functions In Inflammation Resolution and Osteoimmunologymentioning
confidence: 99%
“…63 In steady state, tissue resident Macs seem to be programmed for uptake of dying cells by phagocytosis and elimination through lymphatics in a process called efferocytosis. 84 Efferocytosis is thought to be a critical process in which regulatory interactions between target and effector cells determine its outcome. 85 Efferocytosis induces a phenotypic shift in iMac resulting in conversion to rMac.…”
Section: Mac Functions In Inflammation Resolution and Osteoimmunologymentioning
confidence: 99%
“…This has been confirmed elegantly in a recent paper showing that tissue‐resident macrophages (e.g. in the peritoneum, plural cavity or lung) have a Krüppel‐like factor 2 (KLF2)/KLF4‐driven transcriptomic programme that facilitates apoptotic cell uptake while negatively regulating proinflammatory Toll‐like receptor (TLR) signalling . Similarly, in mouse models of arthritis, tissue‐resident macrophages and monocyte‐derived macrophages exhibit distinct transcriptomic profiles at the peak of inflammation.…”
Section: Synovial Myeloid Cells Are Key Perpetuators Of Inflammationmentioning
confidence: 73%
“…In the RA dataset, almost all methods fail to reach an AUPR > 0.5 regardless of the dimensionality of the latent space. In contrast, for the SLE dataset, all methods see a consistent increase in predictive power as the dimensionality increases, with scCoGAPS and LDA showing the best performance at low (16)(17)(18)(19)(20)(21)(22)(23)(24) and high (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) dimensionality of the latent space, respectively. Taken together, these results suggest that the dimensionality of the latent space is critical for extracting biological features related to the disease state of the cell.…”
Section: Evaluation Of Latent Factor Models Show Differences In Perfomentioning
confidence: 93%
“…We found MERTK-associated pathways to cluster in two main groups ( Figure 4C): one with gene sets related to cell motility and cell signalling, the other one related to endocytosis and phagocytosis. As MERTK is a known marker for endocytic and phagocytic activity (particularly in the context of apoptotic cell clearance 33 ), we set up to assess whether cells that were showing an endocytic-related activity reported an efferocytosis signature 34,35 . We observed that cells characterized by endocytic activity indeed recapitulated this gene signature to a higher degree as compared to the other activity clusters ( Figure 4D).…”
Section: Integration Of Ligand -Receptor Interactions Reveals Mertk-dmentioning
confidence: 99%